Chemical Profiling of Kaliziri Injection and Quantification of Six Caffeoyl Quinic Acids in Beagle Plasma by LC-MS/MS - Changhua Liu; Atikanmu Wahefu; Xueying Lu; Rahima Abdulla; Jun Dou; Haiqing Zhao; Haji Akber Aisa; Xuelei Xin; Yongqiang Liu (MDPI AG, 2022)
Vitiligo is a stubborn multifactorial skin disease with a prevalence of approximately 1% in the global population. Kaliziri, the seeds of Vernonia anthelmintica (L.) Willd., is a well-known traditional Uyghur medicine for the treatment of vitiligo. Kaliziri injections is a Chinese-marketed treatment approved by the China Food and Drug Administration for the treatment of vitiligo. The significant effects of Kaliziri injection have been thoroughly studied. However, chemical components studies and plasma quantification studies are lacking for Kaliziri injection. Ultra-high-performance liquid chromatography coupled with hybrid quadrupole orbitrap mass spectrometry was employed to comprehensively characterize the caffeoyl quinic acid derivatives present in Kaliziri injection. Based on accurate mass measurements, key fragmental ions and comparisons with reference standards, 60 caffeoyl quinic acid derivatives were identified in Kaliziri injections, including caffeoyl quinic acids, coumaroyl caffeoyl quinic acids, dicaffeoyl quinic acids, feruloyl caffeoyl quinic acids, and dicaffeoyl quinic acid hexosides. Moreover, an HPLC-MS/MS method was developed and validated for the quantitative analysis of 5-caffeoyl quinic acid, 4-caffeoyl quinic acid, 1,3-dicaffeoyl quinic acid, 3,4-dicaffeoyl quinic acid, 3,5-dicaffeoyl quinic acid and 4,5-dicaffeoyl quinic acid in beagle plasma. The quantitative HPLC-MS/MS method was applied to quantify these six major caffeoyl quinic acids in beagle plasma after the subcutaneous administration of Kaliziri injection. All of the six analytes reached their peak plasma of concentrations within 30 min.